CHANGE MANAGEMENT IN ENTERPRISES OF THE DAIRY PRODUCT SECTOR OF UKRAINE - VLASENKO, Tetiana; PRUSOVA, Galina; CHUB, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to studying modern trends in the development of Ukraine's milk processing sector. It also reveals the level of actual dairy product consumption by the country's population. As the study results showed, it has been significantly lower than the recommended parameters in recent years. Your role in the dairy sector is crucial to addressing this issue and shaping the future of the industry.The dynamics of milk production volumes by main categories of producers were analyzed. The key structural changes in the industry's development have been identified, among which the most significant is the long-term concentration of production in the sector of small producers—households. In the modern structure of milk production, the share of households in the population is 66%, and 31% is provided by agricultural enterprises of various forms of management.The concentration of production of dairy raw materials within the household sector is accompanied by a low number of problematic issues that hold back the potential of greening, innovative development, and increasing the competitiveness of domestic dairy products. However, there is a silver lining. Strategic orientations for further management changes in the dairy sector of Ukraine's enterprises were outlined, highlighting the potential for organic dairy production. The activation of further development of organic dairy production and the greening of dairy products and trade brands were identified as critical factors. According to the current assessment, the share of organic milk production in EU countries is insignificant. This creates real prospects for Ukrainian dairy companies to increase their competitive potential in the domestic and European milk products market.Based on the research results, a list of the main characteristics inherent in organic production in the country's dairy sector was substantiated. The set of key challenges that necessitate the constant management of changes in the dairy industry enterprises are outlined. The main ones are defined as: structural disparities by category of milk producers, constant complication of dairy product quality standards by the EU, loss of the potential of domestic feed production, low paying demand of the population of Ukraine, slow pace of transformations towards greening and implementation of sustainable development initiatives of the agri-food sector of Ukraine. However, the research results also demonstrated active trends in the development of trademarks of dairy companies in Ukraine, which contributes to a more intensive formation of competitive advantages among them. These findings are crucial for understanding the current state and potential future of the dairy sector, and they also inspire hope for the industry's future.
Keywords: dairy products; management; structural changes; competitiveness; dairy companies; agricultural sector; food security